Relationship between peritumoral brain edema and Ki-67 antigen labelling index in intracranial meningiomas - Al Mahbub, Abdullah; Nath, Haradhan Deb; Esha, Tamanna Ahmed; Habib, Riad; Arifin, Mohammad Samsul (Bangladesh Journal of Neurosurgery, 2026)
Introduction: The most common benign non-glial cerebral tumor in adults is a meningioma. In roughly 50–78% of instances, peripheral brain edema (PTBE) is a common observation in meningioma, while it may not be present in others. Although the Ki67 proliferation index may be able to predict the recurrence of tumors in meningioma patients, there is a lack of conclusive evidence and relationships. Objective: To enhance evaluation, correlate the Ki67 index of meningioma patients with peritumoral cerebral edema. Methods: This cross-sectional study involved 24 patients with meningioma (20 female, 4 male; mean age 39.95 ± 14.54 years). Pre-operative neuroimaging was used to evaluate all patients for the presence of cerebral edema surrounding the lesion using brain MRI and histological confirmation. An immune-histochemical staining known as the Ki-67 index was used to measure proliferative activity. The possibility of a relationship between the levels of the Ki67 index and the existence of PTBE was investigated. Result: WHO grade I tumors were identified in approximately twenty-three (95.8%) of the patients with PTBE, mean age 39.95 with 14.54 SD and male to female ratio 5:1. Eight patients (33.3%) were classified as GR1 patients, one as GR2, and the majority of patients (15/62.5%) as GR0 patients. For G1, the greatest level is represented by the mean value of the Ki-67 Index level, which is 7.00. When compared to gender, tumor location, and meningioma type (p>0.05), the PTBE grading was statistically significant when it came to the Ki-67 indices (p<0.05). Furthermore, the grading of peritumoral edema (PTBE) and the Ki-67 labelling index value exhibited a substantial positive association, as indicated by the spearman correlation test, with a significant p-value <0.05 and a coefficient value of r = 0.647. Conclusion: Peritumoral brain edema (PTBE)-encircled meningioma had a strong correlation with Ki67 indices. Bang. J Neurosurgery 2025; 14(2): 126-131